Influence of organic solvents on cutinase stability and accessibility to polyamide fibers - Silva, Carla Manuela Pereira Marinho da (2005)
ABSTRACT: The stability of cutinase was measured in the presence of imethylacetamide (DMA) and benzyl alcohol (BA). These solvents are known swelling agents of polyamide ﬁbers. We found that cutinase retains some stability (half-life of 14 h), enough for an enzymatic treatment with a solvent composition of 1.5% DMA þ 10% BA. Enzymatic treatment in the presence of these solvent compositions yields more soluble amino groups as well as more amino end groups at the ﬁber level. We have shown evidence that the presence of minor quantities of solvent can increase the accessibility of the enzyme towards the polyamide ﬁber.